Influence of Jackfruit Pulp on the Quality and Shelf Life of Jackfruit Cake - Haque, MA; Begum, R; Shibly, AZ; Sultana, MM; Khatun, A (Journal of Environmental Science and Natural Resources, 2015)
This study was designed to develop cakes incorporating jack-fruit pulp. The seed free jackfruit bulbs blend were used at the level of 10%, 20%, 30% and 40% to prepare jackfruit cake The physical and chemical properties of cakes were analyzed and compared with plane cake (without jack-fruit pulp).The cake containing 10% jack-fruit pulp was best among the samples on the basis of rust and crumb colour and texture of the cakes..The flavours of the cake containing 20% jack-fruit pulp were better than other cakes. The statistical analysis of organoleptic test response of sensory attributes revealed that colour, flavour, taste, texture and overall acceptability werehigher in the cakes containing 10% and 20% jackfruitpulp than normal cake.Shelf life of jack-fruitcakes were decreased with the increased level of substitution of jackfruit pulp during seven day storage on the basis of microbial count.Cake containing 10% jack-fruit showed acceptable physical characteristics, sensory attributes and microbial load. J. Environ. Sci. & Natural Resources, 8(1): 59-64 2015